Pharmacokinetics of NS-105, a Novel Cognition Enhancer - Mukai, Hideya; Sugimoto, Taketoshi; Ago, Masayuki; Morino, Akira (Arzneimittelforschung, 1999)
The absorption, metabolism and excretion of NS-105 ((+)-5-oxo-D-prolinepiperidinamide monohydrate, CAS 110958-19-5), a novel cognition enhancer, were studied in rats, dogs and monkeys after intravenous or oral administration of 14C-NS-105. The protein binding of this drug was also investigated in vivo and in vitro.After the intravenous and oral administrations of 14C-NS-105, the unchanged drug accounted for most of the plasma radioactivity in all the species tested. After the intravenous injection, the plasma concentration of NS-105 decreased monoexponentially with respective elimination half-lives of 0.67, 2.1 and 1.3 h for the rats, dogs and monkeys. After the oral administration, the plasma concentration of NS-105 reached a maximum within 1 h, then decreased as in intravenous administration in all the species tested. NS-105 was almost completely absorbed from the small intestine, and first-pass metabolism was very limited. As a result, its systemic availability was high; 97% in the rats, 90% in the dogs and 79% in the monkeys. No significant sex-related differences in the plasma concentration profiles of radioactivity were observed in the rats after the oral administration of 14C-NS-105 (p > 0.05). Food affected the absorption of NS-105. The Cmax and AUC0-oo of radioactivity concentration were proportional to the dose for 1−100 mg/kg of 14C-NS-105.There were no marked differences between the intravenous and oral routes in the compositions of urinary radioactivity for any of the species tested. In the urine of dogs, LAM-162 (oxidative metabolite with C-N cleavage of the piperidine ring), LAM-79 (metabolite with 4-hydroxylated piperidine ring), LAM-163 (metabolite with 3-hydroxylated piperidine ring) and M1 (not identified) accounted for 20%, 3%, 6% and 1% of the urinary radioactivity, respectively. In the urine of rats and monkeys, LAM-162 and LAM-79 accounted for 1−6% of the urinary radioactivity, but LAM-163 and M1 were not detected.After the intravenous and oral administrations, NS-105 was primarily eliminated by renal excretion in all the species tested, approximately 90% of the dose being excreted unchanged in the urine for rats and monkeys and 60% of it for dogs. Excretions of radioactivity in the bile and exhaled air in rats were less than 1.4% of the dose, and lymphatic absorption of radioactivity was only 0.3% of the dose.The percentage of 14C-NS-105 bound to serum proteins was less than 3.3% in all the animal species tested, including humans.
Keywords: CAS 110958-19-5; Cognition enhancer; NS-105, absorption, dog, excretion, metabolism, monkey, rat; (+)-5-Oxo-D-prolinepiperidinamide monohydrate